The Role of Teachers in Creating an Effective and Enjoyable English Learning Environment in Primary Schools - Tiarnita Maria Sarjani Br Siregar; Seri Wahyuni; Rafly Ahmadizenad; Raisty Khaitami; Herviana; Pardomuan Tanjung (IJESS International Journal of Education and Social Science, 2026)
This literature review examines the role of teachers in creating an effective and enjoyable English learning environment in elementary schools. The study analyzes recent research articles, journals, and academic publications from 2021-2026 to identify key teacher competencies, innovative teaching strategies, and contemporary classroom management approaches that contribute to successful English language learning in the post-pandemic era. The analysis reveals that teachers play a multifaceted role including as facilitators, motivators, digital literacy developers, and socio-emotional learning supporters. Effective teachers employ student-centered approaches, integrate digital technology seamlessly, utilize game-based and project-based learning, create trauma-informed and inclusive learning atmospheres, and demonstrate adaptive teaching practices. The findings indicate that teacher digital competence, socioemotional intelligence, cultural responsiveness, growth mindset orientation, and commitment to continuous professional development significantly impact student motivation, engagement, and learning outcomes. This review provides contemporary insights for educators and policymakers to enhance English language teaching quality in elementary education aligned with 21st-century skills development.